Pengaruh Transformational Leadership, Transactional Leadership, dan Organisational Identification terhadap Job Performance Karyawan PT PLN Persero: Studi Pada Dosen Fakultas Ekonomi dan Bisnis Universitas Trisakti - Fitriyani Fitriyani; Tiara Puspa (Faculty of Economics and Business Diponegoro University, 2025)
This study aims to analyze the influence of transformational leadership, transactional leadership, and organizational identification on job performance among employees of PT PLN (Persero). The background of this research is based on the importance of leadership style and organizational identification in enhancing employee performance, particularly in an increasingly competitive business environment.The study employed a quantitative approach with a census method involving 120 employees of PT PLN (Persero), both at the head office and branch offices. Data were collected through questionnaires and analyzed using multiple linear regression.The results indicate that transformational leadership and organizational identification have a positive and significant influence on job performance. In other words, higher levels of transformational leadership and organizational identification lead to improved employee performance. On the other hand, transactional leadership shows a positive but not significant influence on job performance. These findings suggest that employee motivation at PT PLN (Persero) is more strongly driven by inspiration, individual consideration, and a sense of belonging to the organization, rather than by reward and punishment systems alone.The implications of this study highlight the importance of fostering transformational leadership and strengthening organizational identification as key strategies for improving employee performance. For the management of PT PLN (Persero), these findings can serve as a reference in formulating more effective human resource management policies to support the achievement of organizational goals.